An analysis of the phase status of the red locust, Nomadacris septemfasciata (Serville) in KwaZulu-Natal, South Africa - Bam, Adrian; Conlong, Desmond; Addison, Pia (African Entomology, 2024)
Nomadacris septemfasciata is a true locust species and exhibits phase polymorphism, which can potentially lead to outbreaks and plagues. In a recent outbreak of acridids in sugarcane in South Africa, swarms of N. septemfasciata were observed at increasing densities and displaying colouration indicative of the gregarious phase. The aim of this study was to determine the density-dependant phase polyphenism of populations of N. septemfasciata occurring in sugarcane study sites, based on traditional and geometric morphometric measurements, eye stripes and field observations of hopper colour specimens of N. septemfasciata were collected at three locations from May 2012 to May 2013. Three body characters (length measurements) were measured on 594 individuals and the number of dark vertical stripes on the eyes were counted. Lastly, 100 specimens from two locations (25 males and 25 females from each location) were analysed using geometric morphometrics, based on landmarks on wings. Significant differences in E/F ratios were found between locations and seasons, while wing shape also indicated a significant difference between locations (although small) and wing size (centroid size) showed no significant differences. There was a highly significant difference between wing shape of males and females, and the more gregarious males also exhibited higher E/F ratios in many instances. Eye stripes did not appear to be a reliable character and seemed to contradict the E/F ratio values. To our knowledge, this is the first report of using geometric morphometrics, traditional morphometrics and the number of eye stripes to assess phase polyphenism in adult locusts.